Kode Bahasa, Ragam, dan Struktur Kalimat dalam Iklan Properti di Harian Kompas Edisi April - Juni 2015 Serta Implementasinya dalam Pembelajaran Bahasa di Sekolah Menengah Atas (SMA) - Oktari, Galuh Setya; , Drs.Agus Budi Wahyudi, M.Hum (2016)
This study includes qualitative descriptive. The research objective to (a) identify the form of code language, (b) describe the range of the sentence, (c) the structure of the sentence, and (d) implementation in language learning in high school. This study uses the data 262 in the form of a sentence. Researchers refer to the methods and techniques used in the herd log data. Data analysis method used is the method and the method agih match. The results of the research in the form of code language of advertising the property is (1) Indonesian, (2) English and (3) Indonesian and English. Variety sentence contained in the adverting properties (a) based on the number of clauses that single sentence and compound sentence, (b) based on the shape of a syntax that is declarative sentences (news or statements) and interrogative sentences (ask), (c) based on the shape of the completeness that full sentences and incomplete sentences, and (d) based on the arrangement of the subject-predicate inversion regular expressions and sentences. Single sentence based on the function structured pattern: (1) SP, (2) PS, (3) SPO, (4) SPK, (5) SPPel, (6) SKP, (7) PKS, (8) KSP, (9) SPOK, (10) SKPO, (11) SPPelK, (12) SKPK, and (13) KSPO. The structure of compound sentences: (1) SP+SP, (2) SPPel+SPPel, (3) SP+SPOK, (4) SP+SPPel+KnjSPPel, (5) SP+KnjSPK, (6) SPO+SKPPel, (7) KPS+KnjKSPK, (8) SP(KnjSPO), (9) SPK(SPK), (10) SKPPel(KnjSPOK), and (11) SPOKPel(KnjSPOK). In addition, there is also incomplete sentences which structured S, P and K. Advertising the property may be material and instructional media in High School. Advertising the property can be an interesting learning media students as long as there has been no discussion of the language of advertising property material on school. KEYWORD: Code Language, The Variety of Sentence, Sentence Structure, Sentence, Syntax, Implementation, Education, Advertising The Property